Ethically acceptable consent approaches to adolescent research in South Africa - Marian Loveday; Ameena Goga; Ames Dhai; Melodie Labuschaigne; Theresa Roussouw; Theresa Burgess; Ann Strode; Melissa Wallace; Marc Blockman; Brodie Daniels; Elizabeth Spooner; Linda-Gail Bekker (Southern African Journal of HIV Medicine, 2022)
Background: Adolescents are a unique population with significant unmet health needs. They are often excluded from research that may benefit them as they are perceived as vulnerable and needing protection from research participation. For Research Ethics Committees, conflicting positions in statutes, regulations and ethical guidelines about who provides informed consent for adolescent involvement in health research can be a significant barrier to approving adolescent research. For researchers, the requirement for parental/guardian proxy consent or prolonged approval processes may potentially result in the exclusion of those adolescents most vulnerable and at risk, particularly if issues such as gender-based violence, gender identity, sexuality and sexual practices are in question.